2015
DOI: 10.1134/s1995078015030179
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of reproductive toxicity of multiwalled carbon nanotubes and their putative effects on population ecology of mouselike rodents

Abstract: An assessment of the reproductive toxicity of multiwalled carbon nanotubes (MWCNTs) for male laboratory mice according to a set of morphophysiological, biochemical, and histological criteria is reported. Oral administration of MWCNTs at doses of 0.3, 3, and 30 mg/kg evoked a dose-dependent decrease in the level of free testosterone in blood plasma, as well as a 15-40% decrease in male fertilization capacity. Mathematical modeling allowed for the assumption that a decrease in the parameter named above can induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…Another work by Vasyukova et al. () showed that oral administration of MWCNTs in male mice at doses between 0.3 and 30 mg/Kg could significantly decrease male fertilisation capacity in a dose‐dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Another work by Vasyukova et al. () showed that oral administration of MWCNTs in male mice at doses between 0.3 and 30 mg/Kg could significantly decrease male fertilisation capacity in a dose‐dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Carbone nanotubes Carbone nanotubes (CNTs) have some unique physical and chemical properties and are now being widely used in composite construction materials, ion current sources, microelectronics, and other products. There are proposals on CNTs application as plant growth stimulators [33], agrochemicals carriers [34], agents for controlling rodents-depredators [35], and components of packaging for food products [36]. Data on oral toxicity of both one-wall CNTs and multi-wall ones are fragmentary.…”
Section: Scientific Research Institute Of Nutrition and Rospotrebnadzmentioning
confidence: 99%
“…Data on oral toxicity of both one-wall CNTs and multi-wall ones are fragmentary. There is some evidence that they exert adverse influence on male reproductive sphere [35], and induce an increase in hepatic enzymes levels, antioxidant stress, and unfavorable changes in lipoproteins levels [37]. A lot of effects produced by CNTs in subacute experiments are more obvious under exposure to extremely low doses (less than 0.1 mg/kg of body weight) than high ones (50 mg/kg of body weight and higher).…”
Section: Scientific Research Institute Of Nutrition and Rospotrebnadzmentioning
confidence: 99%
“…Углеродные нанотрубки (УНТ), обладающие рядом уникальных физико-химических качеств, в настоящее время начинают широко использоваться в композитных строительных материалах, ионных источниках тока, микроэлектронике и другой продукции. Имеются предложения по использованию УНТ в качестве стимуляторов роста растений [33], носителей для агрохимикатов [34], средств контроля численности грызунов-вредителей [35], компонентов упаковочных материалов для пищевой продукции [36]. Сведения о пероральной токсичности как одностенных, так и многостенных УНТ фрагментарны.…”
unclassified
“…Сведения о пероральной токсичности как одностенных, так и многостенных УНТ фрагментарны. Получены данные об их неблагоприятном воздействии на мужскую репродуктивную сферу [35], повышении уровней печеночных ферментов, оксидантном стрессе, неблагоприятных изменениях в уровнях липопротеидов [37]. Многие эффекты УНТ в подострых экспериментах сильнее проявляются при их крайне малых дозах (менее 0,1 мг/кг массы тела), чем при больших (50 мг/кг массы тела и более).…”
unclassified